2013
DOI: 10.1371/journal.pone.0076052
|View full text |Cite|
|
Sign up to set email alerts
|

The Incidence and Survival Rate of Population-Based Pancreatic Cancer Patients: Shanghai Cancer Registry 2004–2009

Abstract: BackgroundPancreatic cancer is a devastating disease with dismal prognosis. Large population-based evidence on its survival rate and influence factors is lacking in China.ObjectiveThis study aimed to depict the demographic factors, tumor characteristics, incidence rate and survival rate of pancreatic cancer cases in urban China.MethodsThe demographic factors, tumor characteristics were collected for all the pancreatic cancer cases identified during 2004 to 2009 from the Shanghai Cancer Registry. The survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 22 publications
2
59
2
1
Order By: Relevance
“…Mishra et al found that younger age and female gender were associated with better prognosis 23 . In contrast to that, Tas et al, Worni et al, Gong et al and Luo et al found that shorter survival was associated with older age at diagnosis and male sex 14,16,24,25 .…”
Section: Discussionmentioning
confidence: 83%
“…Mishra et al found that younger age and female gender were associated with better prognosis 23 . In contrast to that, Tas et al, Worni et al, Gong et al and Luo et al found that shorter survival was associated with older age at diagnosis and male sex 14,16,24,25 .…”
Section: Discussionmentioning
confidence: 83%
“…Table IV shows the 5-year observed and relative survival by age group (15-34, 35-44, 45-54, 55-64, 65-74, and 75+) for all the major cancer sites. Relatively higher survival rates were observed in younger patients (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) compared with older patients (65-74, 75+), particularly for sites including the stomach, lung, pancreas, B and CNS, blood (NHL) and cervix. Cancer of the oesophagus, female breast and bladder had higher survival in middle-aged groups (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)…”
Section: Resultsmentioning
confidence: 99%
“…There have been few studies referring to population-based cancer survival in mainland China. Previous studies have reported on population-based cancer survival in Shanghai (38) and Zhejiang (39); however, these studies primarily focused on a certain or some cancer sites over a short time period. In Taiwan, the survival rates for epithelial ovarian cancer and uterine cancer were reported based upon data from a population-based registry (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…This paper attempts to explore part of the patterns and trends hidden behind these published CCRARs. Although a few researchers have performed some secondary analysis using Peng-Lai Chen et al data from certain single CCRAR (Luo et al, 2013), there lack published studies that tried to pool and analyze data from multiple CCRARs.…”
Section: Introductionmentioning
confidence: 99%